Control of seasonal and inter-annual rainfall distribution on the Strontium-Neodymium isotopic compositions of suspended particulate matter and implications for tracing ENSO events in the Pacific coast (Tumbes basin, Peru) - Moquet J.-S. (2020)
The geochemistry of riverine sediments exported to the oceans is important for paleo-hydro-climatic reconstruction. However, climate reconstruction requires a good understanding of the relationship between geochemistry and hydrological variability and sediment sources. In this study, we analyzed the major elements, the strontium-neodymium radiogenic isotopes signatures (87Sr/86Sr and ?Nd) and the mineralogy of the suspended particulate matter (SPM) sampled monthly during two hydrologic years (2007–2008, a wet year, and 2010–2011, a normal hydrological year) upstream the Tumbes River outlet. The hydroclimate of this Ecuador-Peru binational basin is particularly sensitive to ENSO (El Niño Southern Oscillation) events. While mineralogy (dominated by illite) and the chemical alteration index (from 75 to 82) remain almost constant along the two hydrological years, 87Sr/86Sr (0.7115 to 0.7176) and ?Nd (?7.8 to ?1.9) signatures are particularly sensitive to discharge and SPM concentration variations. Along the hydrological year, two sources control the ?Nd variability: (1) volcanic rocks, which dominate during the dry season, and (2) plutonic/metamorphic sources, whose contribution increases during the wet season. This behavior is confirmed by the correlation between ?Nd signature and the monthly rainfall contribution from volcanic area (R = 0.58; p-value < 0.01), and also with the daily discharge at the outlet (R = -0.73; p-value < 0.01). For most of the samples, 87Sr/86Sr is less variable along the hydrological year. However, two exceptional high discharge and SPM concentration conditions sampled exhibit more radiogenic (higher) 87Sr/86Sr signatures when plutonic/metamorphic rocks derived sediments are released in sufficient quantities to notably change the SPM isotopic Sr value of the Tumbes River. Hence, this study demonstrates that 87Sr/86Sr and ?Nd signatures can be used as powerful proxies for paleoclimate reconstructions based on sediment core's analysis in relation with spatial rainfall distribution and intensity in Pacific sedimentary basins submitted to the diversity of ENSO events. © 2019 Elsevier B.V.